Accuracy of transbronchial biopsy as a rebiopsy method for patients with relapse of advanced non-small-cell lung cancer after systemic chemotherapy. Issue 1 (10th January 2017) - Ishii, Hidenobu; Azuma, Koichi; Yamada, Kazuhiko; Matsuo, Norikazu; Nakamura, Masayuki; Tokito, Takaaki; Kinoshita, Takashi; Hoshino, Tomoaki
Abstract : Introduction: Rebiopsy in patients with advanced non-small-cell lung cancer (NSCLC) resistant to systemic chemotherapy may yield information on the mechanisms of resistance and planning of subsequent treatment. Transbronchial biopsy (TBB) using a flexible bronchoscope has been commonly used for establishing the initial diagnosis of lung cancer. The aim of this study was to assess the accuracy and safety of TBB in patients with NSCLC relapse, and the factors affecting its diagnostic yield. Methods: We retrospectively screened patients with advanced NSCLC who underwent TBB for rebiopsy after developing resistance to systemic chemotherapy at Kurume University Hospital between January 2012 and June 2016. A positive diagnostic result obtained by TBB was defined as malignancy determined on the basis of histological features that were adequate for mutational analysis or immunohistochemistry. Severe postprocedural complications were defined as those requiring invasive medical procedures or prolonged hospitalisation. Results: 109 patients were enrolled in this retrospective study. Adequate tumour samples were collected from 88 of these patients, giving a high diagnostic yield of 80.7%. The diagnostic yield of TBB was not associated with tumour mutational status, the previous treatment regimen, or efficacy of the previous treatment. There were no severe postprocedural complications such as pneumothorax or serious haemorrhage. Conclusions: TBB is considered one of the safest and most useful procedures for rebiopsy of NSCLC that has relapsed after chemotherapy, regardless of patient background and treatment history.